Sintering behavior and microwave dielectric characteristics of ZnTiNb2O8 ceramics achieved by reaction sintering of ZnO–TiO2–Nb2O5 nanosized powders. Issue 2 (1st February 2016) - Bafrooei, H. Barzegar; Nassaj, E. Taheri; Ebadzadeh, T.; Hu, C.F.; Sayyadi-Shahraki, A.; Kolodiazhnyi, T.
Abstract: Sintering behavior, microstructure and microwave dielectric properties of ZnTiNb2 O8 (ZTN) ceramics prepared by reaction-sintering method were investigated. The prepared ceramic samples were characterized by field emission scanning electron microscopy, X-ray diffraction, and microwave dielectric measurements. All samples prepared at sintering temperatures ranging from 1025 to 1125 °C exhibit a single ixiolite phase and their relative densities range from ~86.5 % to ~99 %. The variation trend of permittivity and Q × f value was in accordance with variation trend of relative density. Pure ixiolite ZTN ceramic sintered at 1075 °C for 5 h exhibits good microwave dielectric properties with a permittivity about 36.7, Q × f value about 54, 000 GHz, and temperature coefficient of resonant frequency about −70.4 ppm/°C. The obtained results demonstrated that the reaction-sintering process is a simple and effective method to prepare the ZnTiNb2 O8 ceramics for passive microwave dielectric devises.